Mediastinal malposition of catheter after venous cut down - Nasir, Md. Imran; Gupta, Rekha; Gupta, Sanjay; Attri, A. K. (International Surgery Journal, 2018)
Central venous catheterization is one of the very essential tool of modern intensive care. Apart from monitoring the critically ill patient, it helps in administration of antibiotics, parenteral nutrition, chemotherapy, fluids and drug delivery. Peripheral inserted central catheter (PICC) by surgically isolating basilic vein or venous cut down, is considered one of the safe technique to access central veins. The advantage of this procedure is that traumatic complications like pneumothorax, hemothorax and arterial puncture are less as compared to directly placing central catheters. Malposition (intracaval or extracaval) is one of the commonly encountered complication associated with central venous catheterization. Extracaval is rarely encountered and there are isolated case reports in the literature where catheter tip is found outside the central vein into the surrounding structures. Knowledge of such complications is important else these remain unrecognized resulting in delayed treatment and poor outcome. Here, we report a unique case, wherein tip of infant feeding tube inserted from basilic vein was found in anterior mediastinum resulting bilateral hemothorax and pleural effusion.